Analyzing privacy policy languages by specifying HIPAA privacy policies - Cho Lei Win; Phan, Minh Dung; Dailey, Mathew N.; Bohez, Erik L.J.; Norwegian Ministry of Foreign Affairs (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
This research studies privacy policy language by specifying HIPAA privacy policies. The language is illustrated by means of privacy components and represented by HIPAA sample policies. HIPPA privacy rule about use and disclosure of PHI is first formulated in a semi-format forms to generate privacy policies languages like XACML, P3P and EPAL language. We study policy combining mechanisms and their application in HIPAA of XACML. In this research, we evaluate XACML as a particular specification language for HIPAA privacy rules. We also specify P3P and EPAL with the privacy components needed to sufficiently explicit HIPAA privacy rule and compare privacy languages with each other.
A research submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science, School of Engineering and Technology
Research Studies Project Report (M. Sc.) - Asian Institute of Technology, 2015
Keywords: Medical records -- Data processing; XML (Document markup language)